Physiological effectivity and user experience of immersive gait rehabilitation - Hamzeheinejad, Negin; Roth, Daniel; Gotz, Daniel; Weilbach, Franz; Latoschik, Marc Erich (26th IEEE Conference on Virtual Reality and 3D User Interfaces, VR 2019 - Proceedings, 2019)
Gait impairments from neurological injuries require repeated and exhaustive physical exercises for rehabilitation. Prolonged physical training in clinical environments can easily become frustrating and de-motivating for various reasons which in turn risks to decrease efficiency during the healing process. This paper introduces an immersive VR system for gait rehabilitation which targets user experience and increase of motivation while evoking comparable physiological responses needed for successful training effects. The system provides a virtual environment consisting of open fields, forest, mountains, waterfalls, animals, and a beach for inspiring strolls and is able to include a virtual trainer as a companion during the walks. We evaluated the ecological validity of the system with healthy subjects before performing the clinical trial. We assessed the system's target qualities with a longitudinal study with 45 healthy participants in three consecutive days in comparison to a baseline non-VR condition. The system was able to evoke similar physiological responses. The workload was increased for the VR condition but the system also elicited a higher enjoyment and motivation which was the main goal. The latter benefits slightly decreased over time (as did workload) while they were still higher than in the non-VR condition. The virtual trainer did not show to be beneficial, the corresponding implications are discussed. Overall, the approach shows promising results which renders the system a viable alternative for the given use case while it motivates interesting direction for future work.
CRIS-Team Scopus Importer:2021-03-29
Keywords: Centered computing; Human; Human computer interaction (HCI); Interaction paradigms; Virtual reality